Memaknai Dasar Kepemimpinan Yesus Menurut Matius 20:26-28 dan Relevansinya Bagi Pelayanan Pastoral Para Calon Imam (Studi Eksegesis) - Renwarin, Laurensius Malvin; Ngoranubun, Willem (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2023)
The leadership of Jesus is an important archetype in building a Christian community. The basis of Jesus leadership is not into to serve. The basis Jesus leadership is relevant for prsopective priests in carrying out pastoral ministry. The basis of Jesus leadership needs to become a habit to the pastoral life of prospective priests in the midst of the peoplw. Therefore, this paper aims to describe leadership of Jesus according to Matthew20:26-28. The author in this paper uses an exegesis study based on Matthew 20:26-28 with a critical historical method to describe the basis of jesus leadership. The results pf the writining conclude that there are three basic leadership of Jesus in Matthew 20:26-28, including: First, being a servant. Second, The handmaid of the Lord. Third, to give His life. By interpreting the basis of Jesus leadership prospective priests can become leaders who not only rule serve all people in pastoral ministry. Keywords : The leadership of Jesus, being a servant, The handmaid of the Lord, to giveHis life, candidate of priests.